Analisis Soal Ujian Matematika Berkategori Higher Order Thinking Skills (HOTS) Siswa SMP dengan Analisis Rasch Model - Ernawati Ernawati (Jurnal Didaktika Pendidikan Dasar, 2023)
The purpose of this study is to examine the math problems labeled as higher order thinking skills (HOTS) on the test. The elements to be evaluated are organized in a grid for creating test questions, which are then utilized as templates to create test questions after being qualitatively reviewed. The product was subsequently put to the test on Pesawaran's class IX SMP pupils. In this study, the test data were classified as HOTS, and the expert validation result were used to collect the data. There were 18 questions on the HOTS category math test, 15 of which were multiple-choice and 3 of which were short answer. Based on the analysis of the difficulty level of the questions in the field test trials, it found that in multiple-choice question there were eight items in the easy category and seven items in the medium category. In the essay questions, there is one item in the easy category and two items in the medium category.